The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1653/024.101.0304
|View full text |Cite
|
Sign up to set email alerts
|

Can the Environment Influence Varroosis Infestation in Africanized Honey Bees in a Neotropical Region?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Landscape, topography, and climate are relevant environmental drivers that can influence the prevalence of Varroa in honey bee colonies (Chemurot et al, 2016;Giacobino et al, 2017;Correia-Oliveira et al, 2018). Landscape composition has been shown to impact on bee health in general, and in V. destructor loads in particular (Youngsteadt et al, 2015;Giacobino et al, 2017;Kuchling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Landscape, topography, and climate are relevant environmental drivers that can influence the prevalence of Varroa in honey bee colonies (Chemurot et al, 2016;Giacobino et al, 2017;Correia-Oliveira et al, 2018). Landscape composition has been shown to impact on bee health in general, and in V. destructor loads in particular (Youngsteadt et al, 2015;Giacobino et al, 2017;Kuchling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between landscape and Varroa is not clear, because some studies have reported high prevalence of Varroa in colonies where urban land cover dominates (Youngsteadt et al, 2015), while others have described high prevalence of the mite where crops dominate (e.g., Giacobino et al, 2017). Similarly, in relation to topographic and climatic influence, some variables such as altitude, apiaries slope, temperature, and rainfall have been shown to be associated with mite parasitism in honey bees' colonies from tropical and neotropical environments (Chemurot et al, 2016;Giacobino et al, 2017;Correia-Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the absence of well-defined seasons, rain occurrence and its effect on food availability may be more related to infestation rates. Each Brazilian region has specific rainfall characteristics throughout the year, which drastically affects bee flora and brood production, consecutively affecting mite reproductive dynamics (Moretto et al, 1997;Pinto et al, 2011;Correia-Oliveira et al, 2018). Besides environmental effects, a variation in biological features on bees among studied regions may also affect the relation between host and parasite.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, o ácaro Varroa foi detectado pela primeira vez no ano de 1978 (ALVES; FLECHTMANN; ROSA, 1978), e embora as abelhas africanizadas apresentem resistência à patologia, nos últimos anos tem-se despertado preocupação quanto o aumento na taxa de reprodução do ácaro em células de abelhas operárias, quase o dobro quando comparado com a taxa de reprodução no período inicial de surgimento da doença no país. Este aumento significativo pode estar relacionado a mudanças genéticas entre os haplótipos de ácaros encontrados no território nacional (CARNEIRO et al, 2007;GARRIDO et al, 2003;WIESE;SALOMÉ, 2020), e pela ação de mudanças climáticas, fatores A varroatose está presente em todas as regiões do Brasil (GEHRKE;PUKER, 2020;MOREIRA et al, 2017;BARRETO, 2013;PINTO et al, 2015;SCHAFASCHEK et al, 2016), acometendo as abelhas africanizadas, porém, ao contrário do que acontece em outros países, os danos à apicultura brasileira causados por este ácaro ainda são toleráveis (CALDERÓN et al, 2010), pois estas espécies de abelhas desenvolveram rapidamente mecanismo de resistência, denominado de comportamento higiênico de remoção de crias doentes/infestadas (CORREIA-OLIVEIRA et al, 2018). Para mensurar os níveis de infestações nas crias, retirou-se de cada colônia amostral um pedaço de favo contendo crias operculadas (pupas).…”
Section: Introductionunclassified